Roasted jackfruit seed as a potential substitute for chocolate aroma: obtainment, composition, olfactometry, and application - Spada, Fernanda Papa (2017)
Jackfruit seeds are an under-utilized waste in many tropical countries. In this work, we demonstrated the potential of roasted jackfruit seeds to generate chocolate aroma for use as a cocoa substitute in foodstuffs. Twenty-seven different flours were produced from a hard pulp variety of jackfruit by drying (DJS), acidifying (AJS), or fermenting (FJS) the seeds prior to roasting under different time/temperature combinations. The chocolate aroma of groups of four flours were ranked by a sensory panel (n=162) and response surface methodology was used to identify optimum conditions for producing chocolate aroma. Pyrazines were analyzed instrumentally as markers of chocolate aroma, while moisture, pH, and color were also monitored. The best chocolate aroma was produced in three jackfruit seed flours: DJS, AJS, and FJS. Volatile and semi-volatile compound contents were evaluated by GC-MS, GC-O, and SPE-GC in these three jackfruit seed flours and their profiles were compared with the profile of cocoa powder. These flours were also evaluated for their solubility, swelling power, wettability, apparent density, viscosity, sensory preference, and intensity of chocolate aroma. The central composite design was used to optimize the solubility and swelling power. Water temperature and time to flour exposition were the response variables. Owing to their differing volatile compositions, two different flours (DJS and FJS) were applied in six cappuccino formulations with 50%, 75%, and 100% substitution of cocoa powder with jackfruit seed flours. The consumers acceptance of cappuccinos (n=126) and the quantitative descriptive analysis (QDA) were used to describe the preparations. Physicochemical properties in cappuccino formulations were also evaluated. The greatest relative concentration of pyrazines (p<=0.05) was formed in dry, acidified, and fermented flour when we used 156, 165, and 154°C, respectively. Clearly, fermentation is necessary to improve the chocolate aroma of jackfruit seeds, and it is possible to select the best roasting conditions for each treatment to optimize the sensory perception of chocolate aroma. These optimal treatment conditions were found to be 171°C for 47 min in DJS, 180°C for 40 min in AJS, and 154°C for 35 min in FJS. FJS had higher solubility and wettability than other flours. The viscosities of jackfruit seed flours were low with high solubility, properties that are desirable in cocoa powder (CP). Chocolate aroma was most intense for FJS. Therefore, jackfruit seed flours have technological properties and chocolate aroma similar to or better than CP and commercial chocolate (CC). For cappuccino formulations, 50% and 75% cocoa powder was replaced with dry jackfruit seed flour, and there was no change in sensory acceptability or technological properties. The principal component analysis of QDA explained 90% of variance. The primary characteristics of cappuccinos made with dry jackfruit seeds were cappuccino, chocolate, cinnamon, and coffee aromas, and cappuccino and chocolate tastes. Indeed, dry jackfruit seed flour is an innovative cocoa powder substitute; it could be used in food preparations, consequently utilizing this tropical fruit waste by incorporating it as an ingredient in a common product of the human diet.